Análise horária dos elementos climáticos na Paraíba: do descritivo ao geográfico - Araújo, Maressa Oliveira Lopes (2022)
The detailed analysis of atmospheric weather, based on the understanding of its diurnal cycle, is directly related to the organization of daily activities carried out by different social groups. Although relatively scarce, studies that address the hourly variations of climatic elements are increasingly present and are necessary in the analysis of Climatology and related areas. It is considered important to carry out these studies from the most different conceptions of climate, that is, the traditional one (for a more synthetic result for the day-to-day of societies); dynamics (in order to have knowledge about the genesis of climatic phenomena); and the geographic (which puts into practice the rhythmic dynamics based on the historical and excluding reality of the formation of geographic spaces). In face of the exposed, this work has as its primary objective the analysis of the atmospheric behavior of hourly weather elements and their dynamics during events and extreme episodes of rain, in the state of Paraíba, between the years 2009 to 2019. For this, hourly data of the climatic elements were used (precipitation, air temperature, relative air humidity, wind speed and wind direction) from the Automatic Meteorological Stations (AMS) existing in the state, under the responsibility of the National Institute of Meteorology (Inmet). In this stage, significative differences were found between the locations, such as, the closer to the influence of maritimity, the more frequent the rains in the early hours of the day (6 am and 7 am); average temperatures between 22.0ºC and 26.0ºC, approximately; average humidity close to or greater than 70%; and the characteristic winds, mainly, as light or weak breezes and directed from the southeast, east-southeast and south-southeast. For the other locations, where the continentality factor is most prominent, there are: rains in the last and first hours of the day (7 pm, 9 pm, 10 pm, and 1 am), average temperatures between 24.9ºC and 28.0ºC, average humidity between 51% and 61%, and winds varying between light or weak breezes with direction from east and east-southeast. In the second stage, eight hourly rainfall events were selected from the maximum volumes recorded in each analyzed AWS (one for each), in order to understand their genesis and their variability. In this, with the help of journalistic news from the newspaper A União online, it was found that not always high volumes of rain will have an impact on the space in order to generate disasters, defining them as extreme events. However, those that have repercussions the life of society, in this case with occurrence data only in João Pessoa and Patos, were considered as extreme episodes, since the environment was affected and people were placed in a situation of threat. Finally, in the last stage, on a larger scale, in order to obtain more details, a reflective essay was brought to João Pessoa, based on an extreme episode that affected the lives of residents of an area of “very high” degree of socio-environmental vulnerability, which is the Tito Silva Community, located in the Miramar neighborhood, bringing to light how socio-environmental issues, especially in the case of risk areas, need management, development planning and adaptation in the face of imminent and predicted risks in terms of climate. Based on the results, the importance of knowledge about the variability of time atmospheric and climate not only by researchers and governments, but also the whole society, so that mitigating and risk management actions are carried out socio-environmental disasters, such as practices in DRR (Disaster Risk Reduction).